Recurrent AA Amyloidosis Combined With Chronic Active Antibody-mediated Rejection After Kidney Transplantation (Iranian Journal of Kidney Diseases, 2017)
Kidney transplantation for amyloidosis remains a contentious issue. Recurrence of amyloidosis is one of the risks of transplantation. Chronic active antibody-mediated rejection is an important cause of chronic allograft dysfunction. A 47-year-old woman underwent kidney transplantation due to renal AA amyloidosis with unknown etiology. Six years posttransplantation, a kidney biopsy showed AA amyloidosis with chronic active antibody-mediated rejection. Donor-specific antibody class II was positive. The patient underwent intravenous plasmapheresis and treatment with rituximab and colchicine. The relationship between recurrence of amyloidosis and rejection was not obvious. Clinical characteristics of kidney transplantation for AA amyloidosis were subjected to literature review and 315 cases were identified. The incidence of amyloidosis recurrence and acute and chronic rejection rates were 15%, 15%, and 8%, respectively. Five-year patient and graft survival rates were 77% and 82%, respectively. Clinical courses of kidney transplantation in AA amyloidosis were, thus, identified.